Improving the competitiveness of pig producers in an adjusting Vietnam market - International Livestock Research Institute (International Livestock Research Institute, 2010)
Agricultural economist and director of the Livestock Market Opportunities Theme at the International Livestock Research Institute (ILRI), Dr Steve Staal, was interviewed on the Weekend Agro-Products Market programme on VTC-16, Vietnam’s Agriculture and Rural Development television channel. Dr Staal was speaking during a workshop for an ILRI-led project aimed at improving the competitiveness of smallholder pig producers in an adjusting Vietnam market. The workshop was held on 5 October 2010 at the Melia Hotel, Hanoi, Vietnam to mark the end of the project and to present research findings to stakeholders. In this video, he highlights the key findings of the project, noting that smallholder pig producers in Vietnam are indeed competitive and are likely to remain so, especially in light of projected future increases in consumer demand for fresh pork. (From time 15:18). The three year project (2007-2010) was sponsored by the Australian Centre for International Agricultural Research (ACIAR). The project collaborators were the Centre for Agricultural Policy - Institute of Policy and Strategy for Agricultural and Rural Development (CAP-IPSARD), the International Food Policy Research Institute (IFPRI), Oxfam Hong Kong and the University of Queensland.